Análisis morfológico y toxicológico de cultivos de Pseudo-nitzschia pungens var. pungens (Bacillariophyceae) - Sar, Eugenia Alicia (2006)
In the framework of a project of monitoring of harmful diatom species carried out in the Northern area of the Golfo San Matías (Provincia de Río Negro, Argentina) we found and established cultures of Pseudo-nitzschia pungens (Grunow ex. P.T. Cleve) Hasle var. pungens. The strains isolated from net phytoplankton samples obtained in Las Grutas and Piedras Coloradas, (Golfo San Matías) were cultured in F/2 medium, with silica added, and maintained at 20 ºC, under continuous light supplied by cool-white fluorescent tubes. Cultures were essayed for domoic acid (DA) by High Performance Liquid Chromatography (HPLC). Materials from field and cultures were studied with light and scanning electron microscopy. Comparison with closely related taxa, P. pungens var. cingulata Villac and P. multiseries (Hasle) Hasle, and analysis of the fine morphology of cultured material, were conducted and discussed. In spite of P. pungens var. pungens has been reported as domoic acid producer, the toxin was not detected in any of the cultures tested.